The Role of Solar Energy Demand in the Relationship Between Carbon Pricing and Environmental Degradation: A Blessing in Disguise - Khalid Zaman; Sriyanto Sriyanto; Sasmoko; Yasinta Indrianti; Hanifah Jambari; Abdul Rashid Abdul Aziz (Wiley, 2024)
Indexed by SCOPUS/ERA